2016
DOI: 10.3109/19396368.2016.1161864
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone in serum and seminal plasma in comparison with other male fertility parameters

Abstract: Anti-Müllerian hormone (AMH) is a factor most associated with female fertility and especially with the ovarian reserve. AMH is also used as a parameter of fertility in men as it arises from the epithelium of the seminiferous tubules that contain Sertoli cells which produce the AMH. To investigate the relationship between AMH production and sperm related parameters we compared the AMH levels in serum and seminal plasma between a group of healthy males (n=65) and male patients (n=68) of infertile couples with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…The results of this study revealed, for first time, that AMH is present in pig SP, showing average AMH concentration values that were higher than the AMH levels reported in human SP [12,15,18,20]. These results do not come as a surprise when one considers the differences existing in the concentration of other SP-hormones, such as testosterone, between humans and pigs [31,32].…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…The results of this study revealed, for first time, that AMH is present in pig SP, showing average AMH concentration values that were higher than the AMH levels reported in human SP [12,15,18,20]. These results do not come as a surprise when one considers the differences existing in the concentration of other SP-hormones, such as testosterone, between humans and pigs [31,32].…”
Section: Discussionmentioning
confidence: 43%
“…The results of Experiment 1 evidenced a high variability in SP-AMH concentration among boars, which was not linked to their breed. Similarly, variation in SP-AMH between individuals has also been evidenced in humans [14,19,20,36]. Inter-boar variability in other SP-proteins, including other members of the TGFβ-superfamily, has also been reported [8,9,11], and might have a genetic origin [37].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations